Pembuatan Tempat Wudhu Otomatis Menggunakan Sensor Pada Mesjid Al-Anshor Kota Ambon - Wattimena, Sefinath J.; Latuconsina, Rina; Wahyudi, Indra (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Saving water is one of the crucial needs because of the large number of users. It obviously can be seen from availability of clean water in Ambon, especially in the Kebun Cengkeh area, Sirimau District. The fact actually shown from the consumption of clean water from the water tank. This problem frequently occurred in Pinang Putih Puncak, Hative Kecil Village area, the Al-Anshor mosque. The use of manual faucets causes waster wastage. Furthermore, it can spread the virus sticking to the water faucet and it will transfer to another faucet. As a result, it is necessary to install automatic water faucets to prevent the spread of the corona virus and water saving. The method was needs analysis, designing tools, making tools, testing tools, handing over tools to partners and conducting demonstration or socialization of the use of tools. The results have proven, first, the use of this automatic ablution device was very positive and can be used easily.